Respuesta :
Consider the helix below:
[tex]r(t)= (\cos(7t), \sin(7t), -t)[/tex]
We have to determine the value of helix at t = [tex]\frac{\pi}{6}[/tex]
So, [tex]r(\frac{\pi}{6})[/tex]
=[tex](\cos(\frac{7 \pi}{6}), \sin(\frac{7 \pi}{6}), -\frac{\pi}{6})[/tex]
Consider [tex]\cos(\frac{7 \pi}{6}) = \cos(\pi + \frac{\pi}{6}) = - \cos (\frac{\pi}{6}) = \frac{-\sqrt3}{2}[/tex]
Consider [tex]\sin(\frac{7 \pi}{6}) = \sin(\pi + \frac{\pi}{6}) = - \sin (\frac{\pi}{6}) = \frac{-1}{2}[/tex]
So, the value of helix [tex]r(\frac{\pi}{6}) = (\frac{-\sqrt3}{2}, \frac{-1}{2}, \frac{- \pi}{6})[/tex].
We have been given the parametric equation of a Helix as shown below:
[tex]r(t)=\left \langle cos(7t),sin(7t),-1t \right \rangle[/tex]
We are required to find the value of this helix at [tex]t=\frac{\pi }{6}[/tex].
We can do that by substituting [tex]t=\frac{\pi }{6}[/tex] in the given helix equation:
[tex]r(\frac{\pi}{6})=\left \langle cos(7(\frac{\pi}{6})),sin(7(\frac{\pi}{6})),-1(\frac{\pi}{6}) \right \rangle\\r(\frac{\pi}{6})=\left \langle cos(\frac{7\pi}{6}),sin(\frac{7\pi}{6}),-\frac{\pi}{6} \right \rangle\\[/tex]
Upon simplifying this further by using the values of trigonometric ratios, we get:
[tex]r(\frac{\pi}{6})=\left \langle -\frac{\sqrt{3}}{2},-\frac{1}{2},-\frac{\pi}{6} \right \rangle\\[/tex]